Diagnostic properties of the Frontal Assessment Battery (FAB) in Huntington’s disease - Solca, Federica; Aiello, Edoardo Nicolò; Migliore, Simone; Torre, Silvia; Carelli, Laura; Ferrucci, Roberta; Priori, Alberto; Verde, Federico; Ticozzi, Nicola; Maffi, Sabrina; Ceccarelli, Consuelo; Squitieri, Ferdinando; et al. (Frontiers in Psychology, 2022)
Background. This study aimed at assessing the diagnostic properties of the Frontal Assessment Battery (FAB) as to its capability to 1) discriminate healthy controls (HCs) from patients with Huntington’s disease (HD) and 2) identify cognitive impairment in this population. Materials. Thirty-eight consecutive HD patients were compared to 73 HCs on the FAB. Patients further underwent the Montreal Cognitive Assessment (MoCA) and the Unified Huntington’s Disease Rating Scale (UHDRS). Receiver-operating characteristics (ROC) analyses were run to assess both intrinsic – i.e., sensitivity (Se) and specificity (Sp) – and post-test diagnostics – positive and negative predictive values (PPV; NPV) and likelihood ratios (LR+; LR-) – of the FAB both in a case-control setting and to identify, within the patient cohort, cognitive impairment (operationalized as a below-cut-off MoCA score). In patients, its diagnostic accuracy was also compared to that of the cognitive section of the UHDRS (UHDRS-II). Results. The FAB and UHDRS-II were completed by 100% and 89.5% of patients, respectively. The FAB showed optimal case-control discrimination accuracy (AUC=.86-.88) and diagnostic properties (Se=.68-.74; Sp=.88-.9; PPV=.74-.8; NPV=.84-.87; LR+=5.6-7.68; LR-=.36-.29), performing even better (AUC=.9-.91) at identifying cognitive impairment among patients (Se=.73-1; Sp=.86-.71; PPV=.79-.71; NPV=.82-1; LR+=5.13-3.5; LR-=.31-0) and comparably to the UHDRS-II (89% vs. 85% of accuracy, respectively; p=.46). Discussion. In HD patients, the FAB is highly feasible for cognitive screening aims, being also featured by optimal intrinsic/post-test diagnostics within both case-control and case-finding settings.